Open Data Readiness Assessment Prepared for Government of Antigua and Barbuda - World Bank (Washington, DC, 2014)
This 2013 report applies the World Bank Open Data Readiness Assessment Framework to diagnose the readiness of Antigua and Barbuda to create an Open Data initiative. The Framework examines the following dimensions: leadership, policy/legal framework, institutional preparedness, data within government, demand for data, open data ecosystem, financing, technology and skills infrastructure, and key datasets. The report finds Antigua and Barbuda is clearly ready along the dimensions of leadership, institutional preparedness, financing, and infrastructure and skills. Evidence for readiness is present but less clear for the remaining dimensions. The Government stands to benefit from first-mover advantage and has the potential to lead the Caribbean in Open Data, harness skilled people, and establish itself as a world class example of government transparency. An Open Data initiative could also increase efficiency and competitiveness in key areas such as tourism, foreign inward investment, and community engagement. Antigua and Barbuda possesses strengths in its institutions, relevant laws, and high-quality internet infrastructure. However, a successful initiative would require: collective political commitment, leadership, and communication across government; rapid policy development within the framework of existing laws; and demand-side initiatives to stimulate the skilled use of data and the promotion of application development. The report finds that the costs of an Open Data initiative would be modest.